Assessing climate change impact on Guyana's crops using integrated crop and spatial modeling approaches. - Benn, Dina Khadija; Nanlall, Satesh; Jines, Andrés; Eitzinger, Anton (Bioversity International and the International Center for Tropical Agriculture, 2021)
The Crop and Spatial Modeling activity was part of the project ‘Development of an Evidence-Based, Gender Equitable Framework for Climate Smart Agriculture Interventions,’ carried out under the Ministry of Agriculture and in collaboration with the International Center for Tropical Agriculture (CIAT), the Hydrometeorological Service of Guyana, and the University of Guyana. The project required geospatial vulnerability assessment and crop modeling research and extends previous climate change studies and vulnerability and capacity assessments regarding Guyana’s agricultural sector. The research was completed on the comparative use of geospatial methods and crop modeling tools for modeling crop suitability and yield in Guyana. This report shows thematic map outputs that indicate agro-climatic zones of high to low growth potential using current climate and edaphic datasets. Crop modeling required research of the growing conditions of target crops, after which calibrations were applied to estimate yields under future climate scenarios RCP4.5 and RCP8.5.